Electrical properties of metal-insulator-semiconductor (MIS) using low temperature deposition of Zn0 as semiconductor layer / Saifullah Ali Harun - Harun, Saifullah Ali (2013)
This paper investigates the performance of low temperature zinc oxide (ZnO) film as semiconductor and poly(methyl methacrylate) (PMMA) as insulator layer in metal-insulator-semiconductor (MIS) structure. ZnO semiconductor films were grown at different temperatures from 40oC, 60oC, 80oC, 100oC and 120oC. X-ray diffraction (XRD) result revealed that ZnO film grown at 120oC has (002) crystal structure with better crystallinity compared to the other temperatures. Field emission scanning electron microscopy (FESEM) image also show structure transformation of ZnO grain from rice shape to round shape at 120oC. ZnO grown at 120oC show the best electrical properties to be applied as semiconductor layer in MIS devices. The conductivity of MIS increased as the ZnO temperature were increased as deposition temperature increased. The leakage current density for MIS device show that the value increased from 2.0x10-11 A/cm2 to 4.3810-10 A/cm2 as the temperature of ZnO increased. Dielectric properties of MIS indicates that MIS with ZnO grown at 120oC has the highest dielectric constant, k ~ 7.7 measured at 1 kHz. The best characteristics of MIS obtained from the structure with ZnO grown at 120oC due to high conductivity, high crytallinity, good surface morphology and high k value.